Investigation the effect of drought stress on tolerant and resistant rice (Oryza sativa L.) varieties in terms of morphologic and genetic characters - Arvas, Yunus Emre; Yolci, Muhammed Said; Marakli, Sevgi (SPRINGER, 2023)
Drought associated with global warming is a major limiting factor for crop production. This abiotic stress affects the quality and yield of rice (Oryza sativa L.) which is a model organism and also one of the major consumed products all over the world. In this study, we aimed to analyse morphologic (root length, shoot length, root wet weight, shoot wet weight, root dry weight and shoot dry weight) of rice varieties (Dhan 65, Dhan 71, Kiziltan and Karacadag local rice) grown under drought stress during 21 days. For genetic properties, Hopi and Osr30 retrotransposon movements were investigated by using IRAP marker technique. Depending on the decreasing in the amount of water, we observed that all growth parameters showed variable results in four varieties. Moreover, IRAP-PCR indicated different polymorphism ratios among samples. These rates were 0-75% for Hopi and 0-50% for Osr30. As far as we know, this is the first detailed report on dhan 65, dhan 71, kiziltan and Karacadag local rice varieties grown under drought stress.
Keywords: Retrotransposon; IRAP; Polymorphism; Restricted irrigation; Stress tolerance; CULTIVARS; MARKERS; Agriculture; Plant Sciences